Rancang Bangun Jaringan Wireless Local Area Network (WLAN) menggunakan Microtik dan Routing Statik pada MTs Al Barokah Poncowarno Lampung Tengah - Setiawan, Pamuji (Jurnal Sistem Informasi Dan Informatika, 2024)
The development of computer networks today is so rapid. Many organizations and schools use computer networks as a means of completing their tasks. The problem faced is the design of a wireless local area network network that can be installed at the Mts Al Barokah school? The research objective of making this research is to design and create a Wireless Local Area Network (WLAN) network that can connect between computers in building units. This study uses a qualitative approach to determine how to search, collect, process and analyze data from the research. The current system where Mts Al Barokah Poncowano Central Lampung has 20 computers that are connected to each other but do not have internet access, in this case the system is running using a star topology. Devices with one another can communicate with each other smoothly. In implementing a wireless local area network-based computer network at Mts Al Barokah Poncowarno, Central Lampung, using a proxy. The results obtained are that this research is very helpful for Mts Al Barokah Poncowarno, Central Lampung, who previously did not have internet access, now they are connected to the internet and students can take exams at school without having to rent another school's computer, which of course costs money and time.